2008
DOI: 10.1111/j.1399-3054.2008.01166.x
|View full text |Cite
|
Sign up to set email alerts
|

Light and temperature regulation of greening in dark‐grown ginkgo (Ginkgo biloba)

Abstract: The last steps of chlorophyll (Chl) biosynthesis were studied at different light intensities and temperatures in dark-germinated ginkgo (Ginkgo biloba L.) seedlings. Pigment contents and 77 K fluorescence emission spectra were measured and the plastid ultrastructure was analysed. All dark-grown organs contained protochlorophyllide (Pchlide) forms with similar spectral properties to those of dark-grown angiosperm seedlings, but the ratios of these forms to each other were different. The short-wavelength, monome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 65 publications
2
14
0
Order By: Relevance
“…In our previous study we determined the similar amount of Pchlide as Selstam et al (1987) in L. decidua and P. abies (Demko et al 2009). In the case of Ginkgo, the concentration of Pchlide is very low, as was also found by Mariani and Rascio (1982) and Skribanek et al (2008). ALA-synthesizing capacity is poor in the dark.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…In our previous study we determined the similar amount of Pchlide as Selstam et al (1987) in L. decidua and P. abies (Demko et al 2009). In the case of Ginkgo, the concentration of Pchlide is very low, as was also found by Mariani and Rascio (1982) and Skribanek et al (2008). ALA-synthesizing capacity is poor in the dark.…”
Section: Discussionsupporting
confidence: 59%
“…This is consistent with the results that seedlings of G. biloba germinated and grown in darkness showed complete etiolation with no Chl (a+b) ( Table 1). Chinn and Silverthorne (1993) and Skribanek et al (2008) detected also no or little Chl (a+b) in some individuals in dark-grown Ginkgo. Skribanek et al (2008) supposed that little Chl in some individuals came from the embryo via cell division.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Prolonged acclimation could be required to recover for photoperiodic growth. Similar situation was thoroughly investigated in etiolated Ginkgo biloba stems, which are not able to synthesized Chl in darkness (Skribanek et al 2008).…”
Section: Discussionmentioning
confidence: 96%
“…Such unique characteristics of Ginkgo have attracted worldwide interest in plant science research. The genomics (Mohanta 2012) and the physiology (Skribanek et al 2008) of Ginkgo have been thoroughly investigated. Earlier research showed that photo-protection was significantly strengthened at the early stages of leaf expansion in Ginkgo under natural environmental conditions and photosynthetic decline in Ginkgo leaves during natural senescence (Yang et al 2012(Yang et al , 2013.…”
Section: Introductionmentioning
confidence: 99%